The Strategy of Public Relations Through Corporate Social Responsibility Program to Build a Positive Corporate Image - Kurniawan Kurniawan; Nisa Lathifah; Isti Halimah Rosanti (Research Collaboration Community (RCC), 2023)
Corporate Social Responsibility is one of the programs from Public Relations PT Samudera Indonesia Tbk as the social responsibility program for the impact of the environment. The target of this program is RW 11 Kampung Tanjung Priok. The research aims to find out the implementation of the concept of 3P profit, planet, and people, to find out the form of communication channels and communication barriers, and to find out the reason of PT. Samudera Indonesia Tbk chose Kampung Lestari Samudera Indonesia in Corporate Social Responsibility programs to build a positive corporate image. The method of the research was qualitative research with a case studies approach and used the concepts of CSR implementation by Wibisono and the concept of 3P profit, planet, and people by John Elkington. The object of this research is PT. Samudera Indonesia Tbk. The technique used for this research are interviewing, observations, study literature, and documentation. Results of the research showed that at planning stage, Public Relations undertake socializing with RW 11 Kampung Tanjung Priok and making activity plans including make a vision, mission, goals, targets, formulating programs, determining human resources, and providing needs. At implementation stage, the company carried out several activities as installation of Filter Udara, Bank Sampah, and Kebun Gizi. At evaluation stage, Public Relations held an evaluation meeting with Ketua RW 11 and Karang Taruna RW 11 in Kampung Tanjung Priok for the sustainability program, and at the reporting stage, Public Relations make an LPJ report and Karang Taruna make a report of activities results. The communication channels that used by PT. Samudera Indonesia Tbk is a website channel, and the communications barriers that occur are mechanical noise and sematic noise and the company chosen this CSR program as a strategy to build a positive corporate image.